O mito da igualdade de gêneros: compreendendo a insuficiência das cotas políticas para mulheres no Brasil - Silva, Mayra Goulart da (2024)
Despite political gender equality in the legal field, women remain politically underrepresented. In addition to the intense gender imbalance in politics, the few women who enter these institutional areas face women's under-representation in positions of command in the political structure. Thus, this article aims to shed light on the reasons for such gender inequality in these two areas, understanding the role of gender affirmative actions in this frame. Therefore, an analysis was applied involving the changes in electoral legislation and the number of women in the Chamber of Deputies and in command positions at federal and state levels. For this, we separated the theme in four sections, each one approaching different moments and problems.